Multi-omics: Differential expression of IFN-γ results in distinctive mechanistic features linking chronic inflammation, gut dysbiosis, and autoimmune diseases. Issue 111 (July 2020) - Bae, Heekyong R.; Leung, Patrick S.C.; Hodge, Deborah L.; Fenimore, John M.; Jeon, Seon-Min; Thovarai, Vishal; Dzutsev, Amiran; Welcher, Andrew A.; Boedigheimer, Michael; Damore, Michael A.; Choi, Myung-Sook; Fravell, Richard A.; et al.
Abstract: Low grade, chronic inflammation is a critical risk factor for immunologic dysfunction including autoimmune diseases. However, the multiplicity of complex mechanisms and lack of relevant murine models limit our understanding of the precise role of chronic inflammation. To address these hurdles, we took advantage of multi-omics data and a unique murine model with a low but chronic expression of IFN-γ, generated by replacement of the AU-rich element (ARE) in the 3' UTR region of IFN-γ mRNA with random nucleotides. Herein, we demonstrate that low but differential expression of IFN-γ in mice by homozygous or heterozygous ARE replacement triggers distinctive gut microbial alterations, of which alteration is female-biased with autoimmune-associated microbiota. Metabolomics data indicates that gut microbiota-dependent metabolites have more robust sex-differences than microbiome profiling, particularly those involved in fatty acid oxidation and nuclear receptor signaling. More importantly, homozygous ARE-Del mice have dramatic changes in tryptophan metabolism, bile acid and long-chain lipid metabolism, which interact with gut microbiota and nuclear receptor signaling similarly with sex-dependent metabolites. Consistent with these findings, nuclear receptor signaling, encompassing molecules such as PPARs, FXR, and LXRs, was detectable as a top canonical pathway in comparison of blood and tissue-specific gene expression between female homozygous vs heterozygous ARE-Del mice. Further analysis implies that dysregulated autophagy in macrophages is critical for breaking self-tolerance and gut homeostasis, while pathways interact with nuclear receptor signaling to regulate inflammatory responses. Overall, pathway-based integration of multi-omics data provides systemic and cellular insights about how chronic inflammation driven by IFN-γ results in the development of autoimmune diseases with specific etiopathological features. Highlights: Cecal microbiota are distinctively altered by low, but differential levels of IFN-gamma. Robust sex differences in energy and lipid metabolism in ARE-Del mice, associated with gut microbiome and nuclear receptor signaling. Early alteration of B cell and nuclear signaling in the peripheral blood are correlated with later inflammation in the kidney in female homozygous ARE-Del mice. mTOR-autophagy pathway is dysregulated in macrophages at early ages and is an initial pathogenic mechanism in female homozygous ARE-Del mice. Abnormal thymic B cell development and its effect on central T cell tolerance in female homozygous ARE-Del mice is a model for the development of autoimmune disease.